Critical Analysis on the Lesson Plan of the Pre-service Teachers Specializing in Filipino - Fantonial, Rosario; Largo, Rowena (Eximia, 2025)
The mastery of writing a lesson plan is a skill that every pre-service teacher must acquire. The lack of a model guide for developing this skill necessitates the creation of a new model anchored in the socio-cultural theory and the CODE-Plan model, which can address the challenges of pre-service teachers in writing lesson plans. Using both quantitative and qualitative approaches in analyzing the quality of lesson plans and teaching strategies, it was discovered that the quality of lesson plans written by pre-service teachers in Filipino was unsatisfactory. They encountered difficulty in aligning objectives with learning activities, which resulted in poorly designed instructional plans. However, this study also confirmed that the teacher educators themselves demonstrated excellent teaching practices. They possessed broad content knowledge and provided ample opportunities for learners to engage with concepts, enabling them to learn lesson planning skills. The study further revealed a significant relationship between teaching methods and the quality of pre-service teachers’ lesson plans. Effective instruction in lesson plan writing also led to better-quality lesson plans. In conclusion, the lesson plans produced by pre-service teachers exhibited weaknesses and required enhancement of their knowledge on the subject matter, activities, and teaching strategies. Thus, there is a need for a guiding framework that can significantly support the improvement and enrichment of lesson plan development in teaching Filipino.